Answer:
See Explanation
Step-by-step explanation:
Let us assume that [tex] \sqrt 3 - \sqrt 5[/tex] is a rational number.
So, it can be expressed in the form of [tex] \frac{p}{q} [/tex] where p and q are integers.
[tex]\therefore \sqrt 3 - \sqrt 5=\frac{p}{q}[/tex]
[tex]\therefore \sqrt 3 =\frac{p}{q}+ \sqrt 5[/tex]
[tex]\therefore \sqrt 3 =\frac{p+q\sqrt 5}{q}[/tex]
Squaring both sides:
[tex] (\sqrt 3) ^2 =\bigg(\frac{p+q\sqrt 5}{q}\bigg ) ^2 [/tex]
[tex]\therefore 3 =\frac{p^2 +5q^2 +2\sqrt 5 pq}{q^2 } [/tex]
[tex]\therefore 3q^2 ={p^2 +5q^2 +2\sqrt 5 pq}[/tex]
[tex]\therefore 0 = p^2 +5q^2 -3q^2 +2\sqrt 5 pq [/tex]
[tex]\therefore - 2\sqrt 5 pq=p^2 +2q^2 [/tex]
[tex]\therefore \sqrt 5 = \bigg (\frac{p^2 +2q^2}{-2pq} \bigg) [/tex]
[tex]\therefore \sqrt 5 = - \bigg(\frac{p^2 +2q^2}{2pq} \bigg) [/tex]
Since, p and q are integers so [tex] - \bigg(\frac{p^2 +2q^2}{2pq} \bigg) [/tex] is rational.
[tex]\therefore \sqrt 5 [/tex] is also rational.
But it contradicts the fact that [tex]\sqrt 5 [/tex] is irrational.
Hence, our assumption that [tex] \sqrt 3 - \sqrt 5[/tex] is rational is wrong.
[tex] \therefore \sqrt 3 - \sqrt 5[/tex] is irrational.